2014
DOI: 10.1177/1933719113493516
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Allopurinol Reduces Hippocampal Brain Damage After Acute Birth Asphyxia in Late Gestation Fetal Sheep

Abstract: Free radical-induced reperfusion injury is a recognized cause of brain damage in the newborn after birth asphyxia. The xanthine oxidase inhibitor allopurinol reduces free radical synthesis and crosses the placenta easily. Therefore, allopurinol is a promising therapeutic candidate. This study tested the hypothesis that maternal treatment with allopurinol during fetal asphyxia limits ischemia-reperfusion (I/R) damage to the fetal brain in ovine pregnancy. The I/R challenge was induced by 5 repeated measured com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…An animal study in chronically instrumented fetal sheep has shown evidence of cardioprotection and neuroprotection after antenatal allopurinol administration to the pregnant ewe during repeated periods of ischaemia 31 32. In a prospective randomised placebo-controlled pilot study in which allopurinol was administered to the pregnant woman when fetal asphyxia was imminent, we found an inverse correlation between levels of allopurinol and the amount of S100B, a biomarker for brain tissue damage, in cord blood 25…”
Section: Discussionmentioning
confidence: 75%
“…An animal study in chronically instrumented fetal sheep has shown evidence of cardioprotection and neuroprotection after antenatal allopurinol administration to the pregnant ewe during repeated periods of ischaemia 31 32. In a prospective randomised placebo-controlled pilot study in which allopurinol was administered to the pregnant woman when fetal asphyxia was imminent, we found an inverse correlation between levels of allopurinol and the amount of S100B, a biomarker for brain tissue damage, in cord blood 25…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, maternal allopurinol treatment helped to maintain umbilical blood flow and reduced fetal cardiac oxidative stress after ischaemia-reperfusion in fetal sheep 10. Fetal sheep treated with allopurinol also had significantly less neuronal damage in the hippocampal brain area 11. All results from previous research indicate cardioprotective and neuroprotective effects of allopurinol administered to neonates or fetuses during or after perinatal hypoxia 7 8 10–12 35 36.…”
Section: Discussionmentioning
confidence: 85%
“…A recent study in chronically instrumented fetal sheep showed evidence of cardioprotection and neuroprotection after antenatal allopurinol administration to pregnant ewes during repeated periods of fetal ischaemia 10 11. Furthermore, a randomised placebo controlled pilot study in which we administered allopurinol to pregnant women with imminent fetal asphyxia showed an inverse correlation between allopurinol levels and S100ß, a clinically used biomarker for brain tissue damage, in cord blood 12…”
Section: Introductionmentioning
confidence: 94%
“…Animal models including in vivo and in vitro rat models and in vivo sheep models have shown allopurinol to be neuroprotective (50-53). …”
Section: New Potential Treatments For Hi Brain Injurymentioning
confidence: 99%
“…While this single study demonstrates some potential for postnatal allopurinol treatment of affected infants, interest is currently more focused on prenatal treatment, as reactive oxygen species are produced during HI in utero. During intrauterine asphyxia in fetal lambs, maternal administration of allopurinol suppressed superoxide production during intermittent partial umbilical occlusion (56) and decreased fetal hippocampal injury (50), suggesting that providing allopurinol to fetuses at risk for HI may be helpful. In fact, in a randomized double blind placebo-controlled study of 53 pregnant women whose fetuses demonstrated evidence of hypoxia, arterial cord blood from infants of allopurinol-treated mothers exhibited lower levels of S-100B, a marker of brain injury, a very short-term outcome.…”
Section: New Potential Treatments For Hi Brain Injurymentioning
confidence: 99%